2012
DOI: 10.1111/j.1742-481x.2011.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostimulation in the treatment of crural vein ulceration

Abstract: Chronic venous insufficiency, as well as crural vein ulceration, developing at its background, poses a serious clinical problem. Treatment is costly and lengthy. Intense development of physical medicine allows to reduce the time of treatment, as well as to improve the life quality in numerous soft tissue ailments, including wounds that are hard to heal. This article presents the beneficial results of treatment of a 67-year-old woman patient with a diagnosis of crural vein ulceration in the right limb. The appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 4 publications
(5 reference statements)
0
17
0
Order By: Relevance
“… 28 ELF variable magnetic field causes improvement of tissue microcirculation, stimulation of angiogenesis and vasodilatation, as well as stimulation of fibroblasts resulting in increased synthesis of collagen, as well as strong analgesic effect related to local inhibition of inflammation nearby ulceration and stimulation of activity of endogenous opioid system. 29 In turn low-energy light radiation causes among others stimulation of collagen synthesis by activated fibroblasts, improvement of blood supply in tissues nearby ulceration due to vasodilatation effect, and stimulation of lymphatic drainage, as well as strong anti-inflammatory and analgesic effects. 30 …”
Section: Introductionmentioning
confidence: 99%
“… 28 ELF variable magnetic field causes improvement of tissue microcirculation, stimulation of angiogenesis and vasodilatation, as well as stimulation of fibroblasts resulting in increased synthesis of collagen, as well as strong analgesic effect related to local inhibition of inflammation nearby ulceration and stimulation of activity of endogenous opioid system. 29 In turn low-energy light radiation causes among others stimulation of collagen synthesis by activated fibroblasts, improvement of blood supply in tissues nearby ulceration due to vasodilatation effect, and stimulation of lymphatic drainage, as well as strong anti-inflammatory and analgesic effects. 30 …”
Section: Introductionmentioning
confidence: 99%
“…6 In the mechanism of analgesic activity of alternating magnetic fields having low frequency, a substantial role is, among others, that of stimulation of release of endorphins and NO being a transmitter in nerve fibers, which transmit pain stimuli, anti-inflammatory, and antioedematic activities, as well as local improvement in blood supply to tissues in the ulceration area. [15][16][17]44,45 So far, the therapeutic efficacy of both presented methods in the treatment of leg ulcers of various origin has been observed in some published case histories. 4,[19][20][21]46 In the present study, we confirmed for first time that the application It should be emphasized that the time required for a single procedure and the number of procedures in the therapeutic cycle were similar for both analyzed therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In routine clinical practice of our center, two other physical methods are used in the complex treatment of chronic wounds, among them venous leg ulcers magnetotherapy (using extremely low-frequency variable magnetic field as physical therapeutic factor) and light-therapy of collagen, as well as bactericidal and fungicide effect. [15][16][17] Taking into account that therapeutic mechanisms of topical hyperbaric oxygen therapy, magnetotherapy, and light-therapy have similar target points, one can expect that simultaneous action of those physical factors could cause a synergistic effect in the treatment of chronic wounds. Moreover, the progress in biomedical engineering enables the application of those physical factors by a single therapeutic device, supplied with applicator in the form of cylindrical chamber, giving the possibility to treat a leg with venous ulcer separately.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, apart from classical means of treatment, which positively influence the wound healing process, new methods have been introduced in which physical factors are used 68. Among those methods, there is magnetoledtherapy.…”
Section: Introductionmentioning
confidence: 99%